Detection of gaseous species during KCl‐induced high‐temperature corrosion by the means of CPFAAS and CI‐APi‐TOF. Issue 2 (30th August 2019) - Lehmusto, Juho; Olin, Miska; Viljanen, Jan; Kalliokoski, Joni; Mylläri, Fanni; Toivonen, Juha; Dal Maso, Miikka; Hupa, Leena
Abstract: Two different analytical approaches—collinear photofragmentation and atomic absorption spectroscopy (CPFAAS) and chemical ionization atmospheric pressure interface time‐of‐flight mass spectrometer (CI‐APi‐TOF)—were applied to detect and identify the online gaseous KOH and HCl formed in the addressed high‐temperature reactions. Samples of pure KCl, KCl+Cr, KCl+Fe, and KCl+316 L were studied at 550°C under dry and humid conditions with varying oxygen concentrations. The goal was to shed more light on the gas‐phase chemistry during KCl‐induced corrosion under conditions relevant to biomass combustion. CI‐APi‐TOF proved to be a valuable tool for high‐temperature corrosion studies: HCl was identified to have formed during the reactions under humid conditions. On the contrary, despite the known sensitivity of CPFAAS, the formation of KOH could not be verified in any of the performed measurements. Abstract : Two different analytical approaches—collinear photofragmentation and atomic absorption spectroscopy and chemical ionization atmospheric pressure interface time‐of‐flight mass spectrometer—were applied to detect and identify online gaseous KOH and HCl formed in the addressed high‐temperature reactions. Samples of pure KCl, KCl+Cr, KCl+Fe, and KCl+316 L were studied at 550°C under dry and humid conditions with varying oxygen concentrations to shed more light on the gas‐phase chemistry during KCl‐induced corrosion under conditions relevant to biomass combustion.